ANALISIS STRUKTUR MODAL PT SEMEN INDONESIA Tbk - Rina (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
SOE Holding is one of the strategic policies carried out by the Government. PT Semen Indonesia Tbk was appointed as Strategic Holding for BUMN in the cement sector in 2012, with one of the considerations being the potential to increase the funding capability of BUMN Holding which can accelerate growth and expansion thereby increasing productivity. The purpose of writing this scientific paper is to observe the development of the funding policy carried out by PT Semen Indonesia Tbk during 2013-2022. The funding policy is reflected in the capital structure of a company. A review of the capital structure is carried out through the weighted average cost of capital (WACC) approach and leverage ratios in the form of Debt Ratio/DAR, DER, and DTCR at PT Semen Indonesia Tbk for the 2013 period. -2022. The results of the study show that the capital structure fluctuates in a conservative category where the funding policy adopted by management is dominated by own capital/company equity. The level of long-term debt is maintained not to exceed the value of equity